THE ROLE OF PRODUCT INFORMATION IN E-COMMERCE: A CONSUMER-CENTRIC ANALYSIS IN THE MARKETING 5.0 ERA - Yogatama, Ahmad Nizar (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
Shopee has successfully positioned itself as a key e-commerce platform in Indonesia, with a significant and growing number of users. It is worth mentioning that a considerable proportion of Shopee's customer base comprises students from Institut Teknologi dan Bisnis Asia Malang. The phenomenon of young students actively engaging in internet buying is widely acknowledged. The primary objective of this research is to examine the influence of information quality on decision-making processes related to online purchases, specifically focusing on the platform of Shopee. The study utilised qualitative research methodologies, specifically interviews and document analysis, to investigate a sample of 10 students enrolled in the Faculty of Economics and Business at the Institute of Asia Malang. The findings of the study indicate that there are four primary determinants that exert an influence on consumers' decision-making process while engaging in online purchases on the Shopee platform. These elements include the ratings assigned to the stores, the descriptions provided for the products, the reviews received by the stores, and the prices associated with the products. The value of high-quality information in the e-commerce arena is underscored by its potential to facilitate educated purchasing decisions.